Electricity Production from Tofu Whey using Double Chamber Microbial Fuel Cell: Effect of Sodium Acetate - Prasidha, Willie; Alfiansyah Taufiq, Mohammad Rais (ROTASI, 2021)
This study was aimed at evaluating the effect of sodium acetate on the performance of aerated double chamber microbial fuel cells from tofu whey. Six different mass of sodium acetate was soluted in the anode chamber (0, 1, 2, 3, 4, and 5 gr). The value of open circuit voltage (OCV) was taken to analyze the performance. A double chamber microbial fuel cell (MFC) was developed to produce electricity from tofu whey and studied for 1680 hours (70 days). Anode and cathode were made by uncoated graphite rod. After 1680 hours, the electricity production characteristics were obtained. The results show that the highest OCV (274 mV) was reached by adding 5 gr of sodium acetate in the anode chamber. Furthermore, adding 5 gr sodium acetate in the anode chamber could provide more stable OCV then other (0, 1, 2, 3, and 4 gr sodium acetate). From the study can be concluded that adding the sodium acetate in the anode chamber can provide stable and higher OCV.